Do party-states transform by learning? The structural background of the different transformation paths in view of the Romanian, Hungarian and Chinese cases - Maria Csanadi (Hungarian Academy of Sciences, Institute of Economics, 2004)
Through the introduction of a comparative party-state model, I will first demonstrate that due to specific structural and dynamic constraints, the capacity of party-states to learn is both limited and uneven. Differences in the room for manoeuvre are defined by structural and dynamic specifics of power distribution. These will determine the invariable implementation of structurespecific instruments of resource extraction and distribution and their escalation under external pressure no matter the requirements of adaptation. Accelerated implementation of structure-specific instruments leads to different paths of self-destruction rather than adaptation. Adaptation is therefore structurally constrained and self-consuming in party-states. Second,these theoretical arguments will be empirically demonstrated through the economic policy efforts to adapt to market pressures in three radically different party-states - Romania, Hungary by the end of the 1980s and China from early 1990s.
Keywords: 330; party-state systems; communist systems; comparative partystate model; patterns of power distribution; transformation paths; reforms; collapse; Romania; Hungary; China